CHARACTERIZATION OF ANTIOXIDANT ACTIVITY AND TOTAL PHENOLIC COMPOUND CONTENT OF BIRCH OUTER BARK EXTRACTS USING MICRO PLATE ASSAY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In modern plants, 2.7 to 2.8 m3 of solid volume veneer blocks are consumed to produce 1 m3 of plywood. After the hydrothermal treatment and debarking of blocks, waste bark is obtained, which makes up 12.5% of the wood mass, while 16-20% of bark is composed of birch outer bark (BOB). Recalculating, BOB makes up 2.0-3.4% of the veneer log mass. Bark is currently burned in boiler houses that is not rational. BOB contains large amount of valuable extractives (up to 34% from o.d. BOB) consisting of various secondary metabolites such as terpenes, flavonoids, hydrocarbons, polyphenols, tannins etc. BOB extractives exhibit antioxidant properties as well as wound-healing and anti-inflammatory activity. The objective of this paper was to compare amount of total phenolic content (TPC) and antiradical activity (ARA) in ethanol extracts from silver birch (Betula pendula Roth.) outer bark using micro plate assay. Among 11 fractions, fraction of average BOB had the highest DPPH free radical scavenging activity with IC50 of 39.28 μg/mL and the highest TPC 7.42 ± 0.52 g GAE/100 g of dry extract.